Inter-communal cooperation and regional development: The case of Romania - Săgeată, Radu (Wydział Nauk Geograficznych i Geologicznych UAM, 2012)
Romania’s local administrative-territorial organisation shows a high degree of fragmentation. The situation tends to worsen as some villages break away from the parent communes and form new administrative-territorial structures. Since their area is fairly small and adequate financial resources to sustain some coherent, long-term development programmes are missing, a solution would be for them to associate freely into inter-communal cooperation structures, which is a basic prerequisite for attracting European structural funds. Such a type of cooperation practice was experienced in this country at the beginning of the 20th century. Today, inter-communal cooperation could be achieved in two ways: by an association of local communities patterned on historical ‘lands’ (after the French model) and by the establishment of a town, of the metropolitan type, to polarise cooperation structures.
Keywords: administrative fragmentation; inter-communal cooperation; regional development; Romania